MEMAJUKAN UKM CONFETTI DENGAN MEMANFAATKAN TEKNOLOGI DIGITAL - Ardijan Handijono; Rudy Irawan Gunarto; Eka Kusuma Dewi; Samsul Marpitasa; Yunita Kwartarani (Abdimisi, 2019)
Our PKM partners are a family company engaged in the manufacture of T-shirt sheets, which have the trademark "confetti" in Depok area. The problems they face include their limited expertise in utilizing technology for marketing, overlapping employee job descriptions, and financial management which only uses simple bookkeeping.The approach method used in PKM activities is brainstorming to open a mindset about the importance of more professional business management, teaching technology that supports marketing, and making correct financial reports. The solutions offered include proposing the use of current technology, compiling an organizational structure with job description of each role and teaching how to prepare proper financial reports.Keywords: Financial management Digital Marketing, SAAS.